3D search path planning for the blended-wing-body underwater glider. (15th May 2023) - Huang, Hancheng; Liang, Qingwei; Hu, Shanshan; Yang, Cheng
Abstract: A blended-wing-body underwater glider (BWBUG) has the advantages of having low noise and high endurance. As such, it is suitable for underwater search missions. However, the 3D search path planning of the BWBUG faces great difficulties due to the difficulty of accurately establishing the 3D probabilistic sensing model and the complex submarine topography. Therefore, this study proposes a novel multi-stage heuristic method (MSHM) to solve the 3D search path planning problem of the BWBUG. First, a novel 3D probabilistic sensing model is put forward to describe the detection performance of the BWBUG accurately. Second, a model for the 3D search path optimization of the BWBUG is developed by considering the search failure probability, energy consumption, and complex constraints. Then, the MSHM is proposed. This method adopts the position update strategy and multi-stage framework designed in this study, which accelerates the convergence speed and effectively avoids the algorithm from falling into the local optimum. Finally, the simulation experiments and statistical analysis results show that the 3D probabilistic sensing model of the BWBUG proposed in this study is effective. In addition, the MSHM is adequate for the 3D search path planning of the BWBUG, and its comprehensive performance is better than other representative heuristic algorithms. Highlights: A novel 3D probabilistic sensing model of the BWBUG is proposed. A general model for the 3D search path optimization of the BWBUG is developed. The proposed MSHM is adequate for the 3D search path planning of the BWBUG.